Effect of Cryopreserved Rat Embryonic Neural Cells in Intracerebral Hemorrhage Model - Zolotko, Kirill M.; Sukach, Oleksandr M.; Ochenashko, Olga V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 175